IDENTIFIKASI KENDALA DALAM PROSES PRODUKSI DAN DAMPAKNYA TERHADAP BIAYA PRODUKSI PADA UD. RISKY - Sihadi, Intan Purwatianingsih; Pangemanan, Sifrid S.; Gamaliel, Hendrik (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Constraints are activities that prevent companies from carrying out production activities. Along with the increasingly competitive world economy today, industrial companies are required to be more sensitive in anticipating constraints that occur both internally and externally. These constraints must be considered by the company because it can hamper the production process which has an impact on production costs as well as sales volumes which ultimately cause losses to the company. One tool that can identify constraints of a company is the Constraint Theory. This study aims to find out what constraints occur in the production process and the impact of these constraints on production costs. The method used in this study is descriptive. The results of this study are internal constraints are engine damage and external constraints are delays in the delivery of raw materials. The impact of these constraints on production costs is the loss of raw material costs and an increase in factory overhead costs. Keywords: Constraints, Production Cost, Theory of Constraint